Enantioselective determination of acaricide etoxazole in orange pulp, peel, and whole orange by chiral liquid chromatography with tandem mass spectrometry. Issue 4 (February 2015) - Yao, Zhoulin; Li, Zuguang; Zhuang, Shulin; Li, Xiaoge; Xu, Mingfei; Lin, Mei; Wang, Qiang; Zhang, Hu
<x xml:space="preserve">Abstract</x> An efficient enantioselective method for the determination of etoxazole in orange pulp, peel, and whole orange was developed using liquid chromatography with tandem mass spectrometry. The enantioseparation was performed on a Chiralpak AD‐3R column at 30ºC using acetonitrile with 0.1% formic acid solution (80:20, v/v) as the mobile phase in less than 5 min. Quantification was achieved using matrix‐matched standard calibration curves. The overall mean recoveries for two enantiomers from orange pulp and whole orange were 91.0–99.6% and the orange peel was 92.6–103.1%, with relative standard deviations of 0.8–5.4% intraday and 2.0–4.8% interday at 1, 10, and 100 μg/kg levels, and 1.3–5.2% intraday and 3.5–4.3% interday at 5, 50, and 500 μg/kg levels, respectively. The limits of quantification for all enantiomers in three matrices did not exceed 5 μg/kg. Moreover, the absolute configuration of etoxazole enantiomers had been determined by the combination of experimental and predicted electronic circular dichroism spectra, and the first eluted enantiomer was confirmed as (S)‐etoxazole on a Chiralpak AD‐3R column while (R)‐etoxazole was first on three cellulose chiral columns. The application of the proposed method to real sample analysis suggests its potential use in enantioselective determination of etoxazole enantiomers in citrus.